Enhancing Resilience in Indonesian Muslim Families through Logotherapy Counseling - Hunainah Hunainah; Abdul Mujib; Nafan Tarihoran; Aspandi Aspandi; Dody Riswanto; Hilda Syifa Rahma (Bulletin of Counseling and Psychotherapy)
This study aims to evaluate the impact of logotherapy techniques on the resilience of Muslim families, with family status and the number of dependents serving as demographic variables. The study sample consisted of 30 Muslim families in Banten province, Indonesia involving a total of 89 individuals. The sampling using the purposive sampling method consisted of 30 men (father or husband), 30 women (mother or wife), and 29 sons and/or daughters in terms of family status. The study employs a quantitative approach using inferential parametric statistics by using ANOVA. The results obtained indicate logotherapy counseling techniques, such as paradoxical intention, dereflection, and Socratic dialogue, have significantly increased the resilience of Muslim families in Banten. The Paradoxical Intention technique is significant for improving the legal basis dimension and the Dereflection technique is significant for improving the Psychosocial Resilience dimension.  The combined technique of Paradoxical Intention and Socratic Dialogue is significant in improving the other three dimensions of Physical Resilience, Economic Resilience, and Family Social Resilience. More specifically, enhancing physical and economic resilience is best achieved using the paradoxical intention-Socratic dialogue, socio-family resilience with Socratic dialogue-dereflection, legality resilience with paradoxical intention, and socio-psychological resilience with dereflection. In the context of enhancing family resilience, husbands are best served using paradoxical intention-Socratic dialogue, wives by dereflection-Socratic dialogue, and children by paradoxical intention-Socratic dialogue. For families with only child dependents, the most suitable technique is paradoxical intention-Socratic dialogue, while for those with dependents that include children, parents, and/or other close family members, dereflection proves more appropriate.